Adult Literacy and Numeracy Programmes and Labour Market Outcomes - Meehan, Lisa; Pacheco, Gail; Schober, Thomas (New Zealand Work Research Institute (NZWRI), 2023)
Having a basic level of proficiency in reading and mathematics is widely seen as a key factor to fully participate in modern societies. Many developed countries, therefore, have policies to raise the literacy and numeracy skills of adults. In this context, we evaluate adult literacy and numeracy (L+N) programmes in New Zealand. These publicly-funded programmes aim to raise adults’ skills in order to enable further learning and increase the employability and/or workplace productivity of participants. We use population-wide administrative data to estimate the effects of participation on labour market outcomes, further education and training, and workplace accidents, using matching methods to create a suitable comparison group. We examine the effects of three broad types of L+N programmes separately: Workplace LN, Intensive LN and ILN English (for speakers of other languages). For Workplace LN programmes, we find that employment and earnings increases after programme participation. However, employment and earnings actually decrease for Intensive LN and ILN English programme participants. Similarly, social welfare benefit receipt decreases among Workplace LN participants, but increases among Intensive LN and ILN English participants. However, enrolment in education and training increases after programme participation for all three programme types. Moreover, the decreases in employment for Intensive LN and ILN English participants may be due to these increases in education and training participation since a general activity indicator of whether a person is in employment, education or training shows positive results for all three programme types. There is little effect on workplace accident claims.